2011
DOI: 10.1093/nar/gkr572
|View full text |Cite
|
Sign up to set email alerts
|

ChIP-seq reveals cell type-specific binding patterns of BMP-specific Smads and a novel binding motif

Abstract: Dysregulated bone morphogenetic protein (BMP) signaling in endothelial cells (ECs) and pulmonary arterial smooth muscle cells (PASMCs) are implicated in human genetic disorders. Here, we generated genome-wide maps of Smad1/5 binding sites in ECs and PASMCs. Smad1/5 preferentially bound to the region outside the promoter of known genes, and the binding was associated with target gene upregulation. Cell-selective Smad1/5 binding patterns appear to be determined mostly by cell-specific differences in baseline chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
206
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(230 citation statements)
references
References 50 publications
(81 reference statements)
20
206
0
Order By: Relevance
“…5, M-P). The ETS binding motif is enriched in Smad1/5 binding regions in the human genome (51). In this study, we found that endogenous human ETS1 directly bound to the promoter of ID3 in HEK293T cells (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…5, M-P). The ETS binding motif is enriched in Smad1/5 binding regions in the human genome (51). In this study, we found that endogenous human ETS1 directly bound to the promoter of ID3 in HEK293T cells (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…1B). The best-defined SMAD1/5-binding site is GGCGCC, which is present in the enhancers of well-characterized BMP-responsive genes, such as the ID and VENTX genes (Korchynskyi and ten Dijke 2002;Blitz and Cho 2009;Nakahiro et al 2010;Morikawa et al 2011). A lower affinity variant of this sequence, GGAGCC, was also identified in a ChIP-seq experiment investigating BMP-responsive elements in endothelial cells and pulmonary arterial smooth muscle cells .…”
Section: Dna Binding Of Smad Complexes and Its Regulation By Posttranmentioning
confidence: 99%
“…Cells-Numerous BMP target genes have been identified in many types of cells (4,5). Among them, HH family genes, which are targets of BMPs in certain types of cells, play a crucial role in skeletal development (19 -21).…”
Section: Bmp-4 Induces the Production Of Shh In Prostate Cancermentioning
confidence: 99%
“…Phosphorylated Smad1/5/8 form a heteromeric Smad complex with the common-partner Smad (CoSmad), Smad4. This Smad complex translocates into the nucleus, regulates the transcription of various target genes, and exerts a broad range of biological activities (5).…”
mentioning
confidence: 99%